Structural properties of place-labeled Petri net controlled grammars - Mohamad Jan, Nurhidaya; Turaev, Sherzod; Fong, Wan Heng; Sarmin, Nor Haniza (2014)
A place-labeled Petri net controlled grammar is a context-free grammar equipped with a Petri net and a function which maps places of the net to productions of the grammar. The language consists of all terminal strings that can be obtained by parallelly applying of the rules of multisets which are the images of the sets of the input places of transitions in a successful occurrence sequence of the Petri net. In this paper, we investigate the structural properties of place-labeled Petri net controlled grammar related to control Petri nets. We show that removing useless places and transitions does not effect the generative capacity of the pPN controlled grammars. Moreover, we prove that for each pPN controlled grammar, we can construct an equivalent place-labeled ordinary net controlled grammar. Lastly, we show that the hierarchy problem for place-labeled bounded Petri net controlled grammars can be solved effectively.